Functional divergence of Heat Shock Factors (Hsfs) during heat stress and recovery at the tissue and developmental scales in C4 grain amaranth (Amaranthus hypochondriacus) - Goel, Komal; Kundu, Pravesh; Gahlaut, Vijay; Sharma, Paras; Kumar, Ayush; Thakur, Shiwali; Verma, Vipasha; Bhargava, Bhavya; Chandora, Rahul; Zinta, Gaurav (Frontiers in Plant Science, 2023)
Two major future challenges are an increase in global earth temperature and a growing world population, which threaten agricultural productivity and nutritional food security. Underutilized crops have the potential to become future climate crops due to their high climate-resilience and nutritional quality. In this context, C4 pseudocereals such as grain amaranths are very important as C4 crops are more heat tolerant than C3 crops. However, the thermal sensitivity of grain amaranths remains unexplored. Here, Amaranthus hypochondriacus was exposed to heat stress at the vegetative and reproductive stages to capture heat stress and recovery responses. Heat Shock Factors (Hsfs) form the central module to impart heat tolerance, thus we sought to identify and characterize Hsf genes. Chlorophyll content and chlorophyll fluorescence (Fv/Fm) reduced significantly during heat stress, while malondialdehyde (MDA) content increased, suggesting that heat exposure caused stress in the plants. The genome-wide analysis led to the identification of thirteen AhHsfs, which were classified into A, B and C classes. Gene expression profiling at the tissue and developmental scales resolution under heat stress and recovery revealed the transient upregulation of most of the HSFs in the leaf and inflorescence tissues, which reverted back to control levels at the recovery time point. The study reported the identification, physical location, gene/motif structure, promoter analysis and phylogenetic relationships of Hsfs in Amaranthus hypochondriacus. The genes identified may be crucial for future gene functional studies and develop thermotolerant cultivars.